Proposed physiotherapeutic procedure in the treatment of breast cancer - Agnieszka Filarecka; Maciej Biernacki; Michał Jęchorek; Michał Małek; Magdalena Tysowska; Karolina Szymura (Kazimierz Wielki University, 2021)
Breast cancer is a global problem, causes many deaths worldwide, and the emergence of disability resulting from treatment. Physiotherapy is a 24/7 process. It is very often limited to just a few minutes of exercise a day, which is not enough. The aim of the work is to propose physiotherapeutic treatment in women after radical mastectomy and to present diagnostic problems caused by SARS-CoV-2 pandemics, which negatively affect cancer prevention.